PENGANGKATAN ANAK WARGA NEGARA INDONESIA KETURUNAN TIONGHOA DAN AKIBAT HUKUMNYA - Isti sulistyorini (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
According to Western law gives the notion of an adopted child, which is where her emphasis to include children who knew the other children in the family to get the status and function exactly the same with her own child or a determination by the court. In the development of community life suggests  that  the  purpose  of  adoption  is  not  only,  as  mentioned  above,  but  more  than  that, particularly with respect to the legal consequences. Adoption as a legal act can be justified if aimed at the interests and welfare of children, which is caused due to legal inheritance rights acquired an adopted child is one of the main objectives. The purpose of this study was to determine the adoption procedure, the position adopted children related to the legal effect of adoption deed Indonesian citizens of Chinese descent. In  relation  to  the  research  objectives  was  about,  so  in  conducting  research  using  normative juridical  (legal normative  research), which refers  to  the  material library  or  secondary  data. Data sources consisted of primary data sources and data source support (optional), hoping to illustrate the results of a descriptive study on issues related to the procedure and the legal effect of adoption Indonesian citizens of Chinese descent. Keywords: Adoption, procedures, legal consequences.